Lokal Drip: A Coffee Filter Made From Banana Pseudostem - Authors: Camarillo, Bridgette J. Carrera, Mary Jane D. Cielo, Judine De Chavez, Wennie G. Divinagracia, Dreiann H. Mendoza, Ravvie Jaenne M. Rosagaran, Mary Joy T. Santos, Patricia G. 4 0 16; 5 (2023)
Executive Summary: a. Business Description The waste generated by the coffee business is rising and expanding at the same rate as the industry itself in the Philippines as it continues to expand and develop. Lokal Drip was developed by LOKALS in an effort to use less plastic and opt for materials that are compostable and biodegradable. The coffee filter that we will be making is manufactured from banana pseudo-stem, thus the model that is suggested in this study will benefit everyone in the nation by greatly reducing waste and its negative effects on the environment. We developed a version of our regular coffee filter with a Roasted Banana taste or aroma to differentiate it from the competition, enhance the coffee-brewing and consuming experience, and add a wonderful sense aroma to the beverage itself. Due to coffee's increasing popularity across the globe, not only in the Philippines, most people rely on coffee filters to improve their brewing experience. In addition to guaranteeing a smooth and delectable cup of coffee, Lokal Drip will play a significant role in removing impurities and sediments from the beverage. Although there are many coffee filters on the market right now, what coffee enthusiasts actually need is a filter that was designed in accordance with their local environment and is solely focused on improving the coffee-brewing process. By delivering a simple, reliable, but effective design, LOKALS coffee filter strives to give coffee lovers an all-inclusive tool for brewing the perfect cup of coffee. The term LOKALS denotes that the product we will be producing will be made by our locals, our local Filipino laborers, in order to promote and value local Filipinos and highlight their skills and best work when it comes to making coffee filters. This is why the product is called a lokal drip as we are proud to display the craftsmanship of Filipinos. The coffee making or brewing process is depicted in the app's logo, as well as how the coffee drips from the filter and is poured into a cup to create a pleasant experience. lt also uses a combination of very pale orange, very dark brown, and brown to represent the various colours of coffee depending on the type of coffee being brewed. b. Market Analysis Metro Manila coffee shops are our company Lokal Drip's target market. With more 5.630 officially registered coffee shops in the Philippines, with sizable concentration in Manila, the market size for our business is encouraging. The market potential in Metro significant, as there are 956 coffee shops overall. In order to ensure the success of LOKAL Drip in this competitive industry, objective is to establish a strong presence and respond to the unique demands of the coffee shops in Metro Manila. In 2023 with an inventory of 72,572 paper filters, up 43% from the previous year's data (2022) and 70,080 coffee filters delivered. On the other hand, although there is a substantial difference between them in terms of consumer preferences, the predicted growth in the usage of metal coffee filters is practically the same as that of paper filters. Demand for coffee filters increased significantly between 2020 and 2023, rising from 119,324 to 134,393. Between 2023 and 2026, there will likely be an increase in the number of coffee filters, with a demand estimate of 189,236. Lokal Drip seeks to leverage the opportunities coming from this gap by supplying our company with an annual supply-demand gap of at least 90%. c. Market Feasibility LOKAL Drip's brand positioning is focused on providing a sustainable and engaging coffee experience, appealing to both coffee lovers and coffee retailers. In addition to fostering eco-awareness and boosting coffee flavors, LOKAL Drip offers a distinctive and environmentally responsible way to enjoy coffee. LOKAL Drip revenue streams include product sales, which comprise making LOKAL Drip coffee filters available for online purchase via online platform as well as through LOKALS physical store. This guarantees our clients and coffee shops a hassle-free purchasing experience. To cover the convenience of direct delivery to our clients, including coffee shop owners, there is als0 an additional delivery fee in place. In order to create mutually beneficial ties with companies that share our values and target market, we are also actively investigating corporate partnerships as a potential source of revenue. Our commitment to compliance with relevant laws and regulations includes adherence to the requirements of the Food and Drug Administration (FDA) to ensure the safety and quality of our LOKAL Drip coffee filters. We prioritize the highest standards to guarantee the health and satisfaction of our customers, including coffee shop owners. LOKAL Drip is prepared to tap into a developing market in the evolving landscape of eco-conscious consumer choices and desire for a quality coffee experience. We are a formidable challenger in the coffee filter sector due to our unique product, eco-friendly mindset, and diverse revenue techniques. LOKAL Drip's team is committed to following all applicable laws, policies, and regulations in order to provide a seamless and secure experience for our valued clients, including coffee businesses. d. Technical Feasibility The development of Lokal Drip's business across various social media platforms necessitates specific technical management, including the creation and editing of advertisements and digital posters. These materials must effectively capture consumers' attention, ensuring significant exposure, especially during the initial stages. Additionally, there is a need for efficient organization, establishing clear points of contact for addressing FAQs and inquiries. Lokal Drip engages with third-party services such as Lazada, Shopee, and other platforms like TikTok, Facebook, Instagram, and Google to facilitate communication with customers. Customers can easily connect and interact through these applications, enabling them to place orders for delivery or pick up from the physical store-warehouse. Given the widespread use of these communication channels in people's daily lives, navigation is usually straightforward. Moreover, Lokal Drip operates several machines that require regular safety checks to ensure smooth production processes. The business conducts its operations on-site. employing a dedicated team in Metro Manila, specifically in district 4, where the main physical store and warehouse are situated. These operations involve various stages, starting with business prospecting and culminating in the negotiation of terns and conditions to generate revenue. e. Management Feasibility LOKAL DRIP is designed in such a way that new partners may be brought in and departing partners can leave without having a substantial influence on the business's operations. The four members of the group are the partners of LOKAL DRIP. Instead of a basic hierarchy, partners customize the leadership and management structure to match their needs. The company will strictly follow and fulfill all legal requirements to establish a business. LOKAL DRIP will register with the securities and exchange commission Department of Labor and Employment (DOLE) and the Bureau of Internal Revenue (BIR) and also in the Barangay in which the business is located. LOKAL DRIP employees will consistently put their expert knowledge and efforts into the business to keep the company's promise of providing space and equipment for customers; the manager, supervisor, creative staff, and technical staff will be personnel of the business. From Monday-Saturday beginning from 10:00am - 7:00pm, the company's daily operations will be 9 hours in total. The business will require policies to guide its employees in their jobs so they can adequately fulfil their obligations and responsibilities. It also has rules and regulations that must be followed by its employees and customers for everyone's safety. Management will take action if any policy, rule and or regulations are violated. f. Financial Feasibility LOKAL Drip will mostly obtain its funding organically through contributions from individual The feasibility study demonstrates a commitment to current and future stakeholders an shareholders, avoiding interest charges and anticipating inflation to achieve their financial goals and ensure sustainability.
Through a series of assessments using financial analysis with the help of an accountant and supported by research, the financial aspect of this feasibility study demonstrates great potential and competitiveness in aspects such as the ability to generate through careful analysis of financial decisions, the promoters were able to determine the potential effectiveness and profitability of the business process, which led to the creation of a detailed financial plan. g. Socio-Economic Feasibility LOKAL Drip may contribute to government stability, economic growth, and decreasing one of the largest wastes here in the Philippines - banana pseudostem. Its creation enables various opportunities such as job availability, awareness of an eco-friendly coffee filter product, and slowly reducing the synthetic materials in our daily use.
Feasibility Study: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2